درجة امتلاك مدرسي التربية الإسلامية لاستراتيجيات التعلم النشط للمرحلة الثانوية من وجهة نظرهم - محسن علي العكيلي سعد (Journal of College of Education, 2020)
The study aimed to identify the degree to which Islamic education teachers possess active learning strategies for the secondary stage from their point of view, and the study sample consisted of all Islamic education teachers to education Sukkar Castle in Dhi Qar governorate of (145) teachers and schools, In developing a questionnaire and after ensuring its validity and consistency, it consisted of (38) items distributed into three main areas (learning environment, student participation in the learning process, and student performance evaluation). The results of the study showed that the total degree of Islamic education teachers ’ownership in active learning strategies It came with high grades, with a general arithmetic average of (3.711), and the results showed that there were statistically significant differences among teachers of Islamic Education In the degree of their possession of active learning strategies due to the variable of sex and in favor of males, and the results confirmed that there are statistically significant differences among teachers of Islamic education in the degree of their possession of active learning strategies due to the variable of experience and for the benefit of those with long experiences 11 years or more ,The researcher recommended the establishment of training courses for Islamic education teachers for active learning strategies.